The Role Of Case Study Technology In Professional Guidance Of Graduate Students - Mavlonov, Dilmurod Murtazoyevich (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article develops the features of the use of case study methods in pedagogical activities. The main purpose of case study technology is to develop their scientific and creative abilities by solving educational didactic tasks and existing problem situations. The article discusses one of the educational methods, the "Case Study" method, to connect knowledge in the field of biology with everyday life, develop students' thinking skills, and increase teaching efficiency, provides examples of it, and discusses the types of cases related to the science of human anatomy.